2017
DOI: 10.1097/md.0000000000006222
|View full text |Cite
|
Sign up to set email alerts
|

A three-long noncoding RNA signature as a diagnostic biomarker for differentiating between triple-negative and non-triple-negative breast cancers

Abstract: Background:Triple-negative breast cancer (TNBC) is an aggressive cancer with unfavorable outcome and it is useful to explore noninvasive biomarkers for its early diagnosis. Here, we identified differentially expressed long noncoding RNAs (lncRNAs) in blood samples of patients with TNBC to assess their diagnostic value.Methods:Differential expression of lncRNAs in plasma of patients with TNBC (n = 25) and non-TNBC (NTNBC; n = 35) and in healthy controls was compared by microarray analysis and validated by real-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
50
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(61 citation statements)
references
References 40 publications
(43 reference statements)
3
50
0
1
Order By: Relevance
“…LncRNAs were considered as non-protein-coding transcripts longer than 200 nucleotides and widely expressed in various organs and tissues of the body [14-16]. Functional lncRNA was involved in various cancer biological processes, such as proliferation, apoptosis, invasion and metastasis through modulation of chromatin remodeling, epigenetics modification, regulation of gene transcription, post-transcriptional mRNA processing, protein function and localization, and intercellular signal transduction regulation [17].…”
Section: Introductionmentioning
confidence: 99%
“…LncRNAs were considered as non-protein-coding transcripts longer than 200 nucleotides and widely expressed in various organs and tissues of the body [14-16]. Functional lncRNA was involved in various cancer biological processes, such as proliferation, apoptosis, invasion and metastasis through modulation of chromatin remodeling, epigenetics modification, regulation of gene transcription, post-transcriptional mRNA processing, protein function and localization, and intercellular signal transduction regulation [17].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, simultaneous evaluation of tumour‐associated circulating lncRNA panel may increase the sensitivity and specificity of diagnosis and prognosis in breast cancer. Towards this direction, one recent study using a small cohort has demonstrated that a three‐lncRNA signature, including ANRIL, HIF1A‐AS2 and UCA1, can serve as diagnostic markers for differentiating between triple‐negative and non‐triple‐negative breast cancer . Evidently, further systematic and multicenter studies of larger independent samples are urgently needed to develop the possible clinical applications of circulating lncRNAs in patients with breast cancer.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, it has been found that lncRNAs may be expressed either ubiquitously or in a tissue-specific manner [39] and that they may be released in a stable form into the bloodstream during the course of the disease. Accordingly, Liu et al [40] recently observed a good correlation between the levels of three lncRNAs (ANRIL, HIF1A-AS2 and UCA1) in plasma and tumor tissues of patients with TNBC. Additionally, our group recently identified three circulating lncRNAs (GAS5, ZFAS1 and RMRP) that were found to be deregulated in patients with advanced breast cancer [41].…”
Section: Lncrnas and Breast Cancermentioning
confidence: 96%